THE ROLE OF INGUSHETIA’S INTELLIGENTSIA IN THE GREAT PATRIOTIC WAR - Dzarahova, Z M-T (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the participation of the intellectuals of Ingushetia in the Great Patriotic War. The fact is that even during the most difficult days and years of the war the intellectuals did not forget about their professional functions: they taught, treated, designed, and researched. The leaders of the country saw the main task of the intellectuals in mobilization of spiritual power of the people and formation of intolerance against the fascist invaders.